As Doze Valsas de Esquina de Francisco Mignone: um estudo técnico-interpretativo a partir de suas características decorrentes da música popular - Marcelo Novaes Machado (2004)
The Doze Valsas de Esquina (The Twelve Street Corner Waltzes) byFrancisco Mignone are impregnated by the romantic atmosphere of the serenades and the chorinho1 and their most used instruments, the flute and the guitar. The composer was inspired by memories of his youth when he used to write and play popular music in movie theaters, balls and serenades by the street corners of São Paulo city. He has brought to classical music, an improvisation style and traces of popular music and of a nationalized waltz, then serving to the purposes of the strong Brazilian National Modernism of that time. This study intends to identify some of these improvisational elements and traces of popular music in these waltzes, as well as to emphasize the importance of an acknowledgement and previous and intense performer`s contact with this kind of music for the performance.